Some old problems with the new guidance on counselling people of African ancestry - Young, Charles (PINS-Psychology in Society, 2025)
Mpofu, Elias (ed) (2011) Counseling people of African ancestry. New York: Cambridge University Press. ISBN 978-0-521-88722-9 hbk. Pages xix + 332. The purpose of this book is an ostensibly worthy one, which is to promote Afrocentric understandings and culturally sensitive mental health interventions for Africans and people of African ancestry. The latter includes descendants of the African diaspora – whose ancestors were scattered across the globe, often by violent force, and who retain a cultural affiliation with their ancestral origins.